PERLINDUNGAN HUKUM BAGI PETUGAS PEMASYARAKATAN DALAM MELAKSANAKAN TUGAS TERHADAP WARGA BINAAN PEMASYARAKATAN YANG MELAKUKAN TINDAK PIDANA DILEMBAGA PEMASYARAKATAN (STUDI DI LEMBAGA PEMASYARAKATAN KLAS II A PONTIANAK) - NIM. A2021161073, SYECH WALID S, SH (Jurnal NESTOR Magister Hukum, 2019)
ABSTRACT This thesis discusses the diversion of narcotics crime against children (Case Study In Sambas District). From the results of this thesis research obtained the conclusion that the Implementation of Diversity Against Children Perpetrators of Narcotics Crime Based on Law Number 11 Year 2012 About Child Criminal Justice System. In the review of the legal position of the diversion of drug abusers of children in the perspective of the development of law pidanamerupakan non-penal policy measures handling criminal child friendly, because handling is diverted from the path of the juvenile justice system. Diversion start from the assumption that the process of the treatment of children through the juvenile justice system is more likely negative than positive for the development of drug abusers anak.Berkaitan with penanganananak, main problems arising from the criminal justice process child or a criminal verdict is stigma attached to convicted drug abuse after Finished criminal justice process. The tendency to increase the abuse of narcotics by children, to encourage efforts to overcome and handling it specifically in the field of child criminal law.Diversion start from the assumption that the process of the treatment of children through the juvenile justice system is more likely negative than positive for the development of drug abusers anak.Berkaitan with penanganananak, main problems arising from the criminal justice process child or a criminal verdict is stigma attached to convicted drug abuse after Finished criminal justice process. The increasing tendency of drug abuse by children, encourages the effort of handling and handling it specifically in the field of child criminal law. Diversi with Restorative Justice approach in its development is a settlement of child crime cases that have been practiced by various countries, including in Indonesia as stipulated in Law no. 11 Year 2012 on the Criminal Justice System of Child and Government Regulation no. 65 The year 2015. The concept of diversion set forth in the Indonesian Criminal Justice System is the obligation to undertake Diversity at every stage of the judicial process (Investigations, Prosecutions and Courts). The arrangement of diversion in the direction of narcotics perpetrators for the future of the implemented diversion concept In Indonesia is only a component of the improvement of the structure of the Criminal Justice System as an alternative to formal criminal justice, by placing Diversity efforts at every stage of the judicial process (Investigation, Prosecution and Courts). The concept of diversion is not much different from the divergence concept applied in Australia, Police Diversion. This is based on the consideration of the Police as the first gate to handle children in conflict with the law to determine whether a child will proceed to the judicial or other informal proceedings such as penal mediation. In relation to the handling of child abuse drug narcotics police as the discretionary authority holder should conduct Diversity through the program Medical rehabilitation and social rehabilitation without being faced with a criminal justice process.Keywords: Diversity, Crime, Narcotics, Children. ABSTRAK Tesis ini membahas tentang Perlindungan Hukum Bagi Petugas Pemasyarakatan Dalam Melaksanakan Tugas Terhadap Warga Binaan Pemasyarakatan Yang Melakukan Tindak Pidana Dilembaga Pemasyarakatan (Studi Di Lembaga Pemasyarakatn Klas II A Pontianak). Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Bentuk perlindungan hukum saat sekarang ini bagi petugas pemasyarakatan dalam melaksanakan tugas terhadap warga binaan pemasyarakatan yang melakukan tindak pidana di lembaga pemasyarakatan ialah pelaksanaan Pasal 3 Undang-Undang Nomor 12 Tahun 1995 Tentang Pemasyarakatan oleh petugas pemasyarakatan dalam kaitannya dengan warga binaan yang melakukan perbuatan melawan hukum di Lembaga Pemasyarakatan Klas II A Pontianak. Pemasyarakatan sebagai tujuan pidana diartikan sebagai pemulihan kesatuan hubungan hidup, kehidupan dan penghidupan yang hakiki, yang terjadi antara individu pelanggar hukum dengan masyarakat serta lingkungan kehidupannya. Pemasyarakatan adalah kegiatan untuk melakukan pembinaan warga binaan pemasyarakatan berdasarkan sistem, kelembagaan dan cara pembinaan yang merupakan bagian akhir dan sistem pemidanaan dalam tata peradilan pidana. Kualitas petugas termaksud di dalamnya kualitas kesejahteraan merupakan satu hal yang sangat dominan dalam mempengaruhi kinerja pemasyarakatan. Dan hak-hak dari para petugas pelaksana terutama hak untuk mendapatkan perlindungan dan memperoleh kenyamanan dalam bekerja.Bentuk perlindungan hukum bagi petugas pemasyarakatan dalam melaksankan tugas terhadap warga binaan pemasyarakatan yang melakukan tindak pidana dilembaga pemasyarakatan pada masa yang akan datang ialah kejelasan kedudukan dan fungsi perlindungan hukum bagi petugas pemasyarakatan, kebijakan-kebijakan yang dilakukan dalam pelaksanaan tugas pemasyarakatan, kejelasan hukum jaminan perlindungan hukum terhadap petugas pemasyarakatan serta Pembaharuan atau Rancangan Undang-Undang yang mengatur Bentuk perlindungan hukum bagi petugas pemasyarakatan dalam melaksankan tugas terhadap warga binaan pemasyarakatan yang melakukan tindak pidana dilembaga pemasyarakatan untuk masa yang akan datang harus ditempuh dengan pendekatan yang berorientasi pada kebijakan (policy-oriented approach) dan sekaligus pendekatan yang berorientasi pada nilai (value-oriented approach) karena ia hanya merupakan bagian dari suatu langkah kebijakan atau policy (yaitu bagian dari politik hukum/penegakan hukum, politik hukum pidana, politik kriminal, dan politik sosial).Kata Kunci : Perlindungan Hukum, Petugas, Pemasyarakatan.